A model-based process for the modelling and the analysis of avionic architectures. (2017) - Ouhammou, Yassine; Long, Anh-Toan Bui; Grolleau, Emmanuel; Bauer, Henri; Ridouard, Frédéric; Richard, Pascal; Richard, Michaël
To design and analyse integrated modular avionics (IMA) architectures, this paper presents a model-based process with separation of concerns going from the business view to the scheduling analysis view. A pivot meta-model dedicated to schedulability analysis has been extended to support recent and new systems architectures as well as new analysis methods. This pivot meta-model represents the front-end of a design framework filling the gap between the system architect and the schedulability analysis expert. This is presented in this paper by showing how the design framework is used to handle IMA architecture, and how simple plugins were developed and connected to the framework. The plugins propose hierarchical schedulability analysis, as well as end-to-end response-time analysis for network architecture. This research is illustrated by discussing a case study.